DENTAL ANXIETY AND FEAR IN PRIMARY HEALTH CARE: A SYSTEMATIC REVIEW OF CHALLENGES AND CARE STRATEGIES - Anne Camile Fontenele de Castro; Cecília Maria Marinho Holanda; Lia Labourê Gonçalves Cardoso; Gabriela Amaral de Moura Petkevicius; Valber Jones de Castro; Marta Maria do Socorro Lima Barros Gonçalves; Valder de Castro Júnior; Janevane Silva de Castro (Veredas do Direito, 2026)
Anxiety and fear related to dental treatment are significant barriers to accessing and maintaining oral health care—particularly in primary care settings—as they are associated with missed appointments, worsening health conditions, and the need for more complex treatments. This study aims to examine, through a systematic literature review, the main challenges associated with dental anxiety and fear, as well as the management strategies employed. The methodology involved searching, selecting, analyzing, and discussing scientific articles from the PubMed and Web of Science databases, using keywords related to dental anxiety, fear, and primary care, with a focus on recent, full-text studies. The results indicated that managing dental anxiety can involve various approaches, emphasizing non-pharmacological interventions—such as behavioral techniques, music, virtual reality, and sensory strategies—alongside pharmacological interventions in specific cases. It was observed that no single approach is universally effective; rather, tailoring care to the individual and combining different strategies are crucial factors for achieving better clinical outcomes. In conclusion, early detection of anxiety and the implementation of patient-centered approaches are essential for improving the quality of care and increasing adherence to oral health care.